Supporting Department Chair Development: Learnings from the Leadership Cohort - Emily R. Smith; Ryan Colwell; Patricia E. Calderwood (Academic Chairpersons Conference Proceedings, 2018)
This best practice presentation will highlight key features, benefits and challenges of a cohort-based leadership development program for chairs. We’ll engage with sample materials and activities used during cohort meetings and share recommendations for those looking to initiate leadership development programs on their campus.
Keywords: Leadership development; cohort models; chair support; co-mentoring; teaching and learning centers